C.T.P.C. Papers Nos. 1 - 100 Vol. I - Planning Commission (Planning Commission, 1959)
The Road Transport Reorganisation Committee set up by the Government of India (Ministry of Transport and Communications) in May 1958 was entrusted with the task of surveying the existing machinery for the administration of motor transport in the States with a view to suggesting a model administrative set up which inter alia would ensure the growth of the industry consistent with' the economic development of the country.
Transport Division Planning Commission
Transport Division Planning Commission